Scoping the Impact of Digitalization - Milla Wirén (United States, 2022)
While the scholarly understanding of the representation level entities (like platforms, social network systems, and industrial internet) of digitalization is already nascent, the deeper drivers of the phenomenon are still notably ignored in IB research. This article explicates three funda- mental drivers (datafication, digitizing and connectivity) of the socio-technical phenomenon labelled digitalization, and further explores the potential impact scope of those drivers through utilizing an analytical tool (Causal Layered Analysis, CLA) adopted from the field of futures research. In doing so, the article contributes to the scholarly discussions attempting to unravel and understand the contemporary socio-economic turbulence, especially through viewing the role of technological advances in transforming the economic landscape. It is the claim of this article that without understanding the role and potential impact of technological advances, ex- planations grounded on political, social and economic trajectories do not yet yield a full picture of the current changes in the international business environment.